Platelet Indices in Pregnant and Non Pregnant Females: A Comparative Study at a Tertiary Care Diagnostic Laboratory - Nayyar, Muhammad Wasi; Mahmood, Asad; Zohra, Sadaf; Khurshid, Ayesha; Ali, Sadia; Zahir, Saima (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the platelet indices in pregnant and non-pregnant females at a tertiary care diagnostic laboratory.Study Design: Comparative cross-sectional study.Place and Duration of Study: Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jul to Dec 2020.Methodology: 166 healthy pregnant females were included in group-1, and 166 non-pregnant healthy females were recruited in group-2. 5 ml of fresh venous blood from the antecubital vein was collected under aseptic conditions in EDTA anticoagulant tubes. This sample was analyzed to determine complete blood counts (TLC, RBC, HB, and Platelet Count) and platelet parameters, namely Platelet distribution width (PDW), Mean platelet volume (MPV) and Plateletcrit (PCT), using an automated haematology analyzer Sysmex XN-3000.Results: A total of 332 patients with a mean age of 26.5 ± 5.12 years were included in the study. Platelet count, PCT and PDW values were higher among group-2 than the pregnant females (p=0.001). MPV was higher among the group-1 females than the group-2 females (p=0.001). The distribution of platelet parameters across the trimesters showed that platelet count and PDW among the trimesters showed a statistically significant difference (p=0.001).Conclusion: Pregnancy brings along many physiological changes in the female body. Various haematological and biochemical changes accompany these changes. MPV, PDW and PCT values were decreased in the pregnancy group. However, MPV was found to be increased as compared to group-2.